Architects of our own destiny : profiling opportunities for reconciliation and restorative justice within the context of the Presidential Urban Renewal Programme in Mitchell's Plain - Esau, Matthew (Department of Religious Studies, 2014)
Includes bibliographical references (leaves 103-107).